Crashing the party: advocacy coalitions and the nonpartisan primary. (8th November 2017) - Sinclair, J. Andrew; O'Grady, Ian; McIntosh, Brock; Nordlund, Carrie
Abstract: California and Washington recently replaced traditional partisan elections with nonpartisan "top-two" election procedures. Some reform advocates hoped that voters would behave in a way to support moderate candidates in the primary stage; the limited evidence for this behaviour has led some scholars to conclude that the reform has little chance to change meaningful policy outcomes. Yet we find that the nonpartisan procedure has predictable and disparate political consequences: the general elections between two candidates of the same party, called copartisan general elections, tend to occur in districts without any meaningful crossparty competition. Furthermore, copartisan elections are more likely to occur with open seats, when a new legislator will begin building a network of relationships. The results, viewed through the lens of the Advocacy Coalition Framework, suggest that opportunities exist for coalitional rearrangement over time.